Analisis Makna Simbol Batu Tallu dan Täbä Tallu Tentang Pemeliharaan Allah di Salutambun dengan Menggunakan Teori Ernst Cassirer - Jeffri Andri Saputra (Institut Agama Kristen Negeri Toraja, 2020)
Batu and Täbä are symbols and cultural relics in Salutambun. The main ideas represented through Batu and Täbä were the providence of God in the history of the local people. Reviving this meaning is the main purpose of the author. The last few decades after the community was dominated by Christianity, the center of community attention switched to the background of symbol founders (non-Christians) and the emergence of the title of